The Social Legacy of AIDS: Fertility Aspirations Among HIV-Affected Women in Uganda - Snow, Rachel C.; Mutumba, Massy; Resnicow, Kenneth; Mugyenyi, Godfrey Rwambuka (American journal of public health, 2013)
Before the availability of antiretroviral therapy (ART) in Africa, women infected with HIV not only had reduced fecundability,1---4 but also reduced fertility aspirations as many women, men, and health providers were opposed to continued childbearing by persons infected with HIV.5---7 Qualitative studies reported that HIV-positive women were generally anxious to prevent conception,5,6 and a majority of both men and women were planning fewer children because of AIDS.8 In one study, only 10% of HIV-positive home-based care clients reported that they wanted more children.9 Fertility aspirations varied by context and location,5,10,11 but they were diminished by the perceived risk of perinatal transmission,5,11 fear of dying and leaving children behind,8,12 and by the previous death of a child,8,13 and weighed against the underlying desire for children and the need to avoid childlessness or cement a relationship. 6,8,10 An early study in pretreatment Rwanda, for example, described a marginal decline in pregnancies among HIV-positive women, shaped in part by health fears, but also by whether women had achieved a desired fertility norm. As access to ART increased, several studies documented a rebound in fertility desires. This included a 2005---2006 study of 501 HIV-positive women in Mbarara, Uganda (the same location as the current study), which found fertility desires positively associated with use of ART, and inverse to the World Health Organization (WHO) stage of illness. In South Africa, Cooper et al. reported that HIV-positive patients (without access to care) felt that access to therapy for the prevention of mother-to-child transmission and ART would lead them to reconsider having children13; in 2009 the same authors modeled these effects, reporting that use of ART restored fertility desires among HIV-positive women, but not HIV-positive men. Rebounding fertility desires were subsequently borne out by a documented increase in the incidence of pregnancy after ART across multiple African countries.